Effect of Trial of Labor before Cesarean and Risk of Subsequent Placenta Accreta Spectrum Disorders - O'Malley, Katharine N.; Norton, Mary E.; Osmundson, Sarah S. (American Journal of Perinatology, 2020)
Objective This study aimed to examine whether labor before cesarean affects the risk of placenta accreta spectrum (PAS) disorders in a subsequent pregnancy.Study Design This is a secondary analysis of the Cesarean Registry, a prospective cohort study of women undergoing cesarean between 1999 and 2002. Women with one prior cesarean with known indications, which were categorized as likely associated with labor (labored cesarean) versus likely not associated with labor (unlabored cesarean), were included. Primary outcome was PAS disorder.Results Of 34,224 women, 60% had a “labored cesarean” and 40% had an “unlabored cesarean.” Women with prior unlabored cesarean were more likely to have subsequent PAS disorder compared with women with a prior labored cesarean after adjusting for confounders (0.28 vs. 0.13%; adjusted odds ratio: 2.03; 95% confidence interval: 1.22–3.38).Conclusion Prior unlabored cesarean is associated with an increased risk of PAS disorders in a subsequent pregnancy. This association may aid in risk stratification in women with suspected PAS disorders and help counsel about risks associated with cesarean on maternal request.
Keywords: placenta accreta spectrum disorder; prior cesarean; obstetric complications; risk stratification